Le rôle de l’environnement physique arctique sur l’évolution du Tunumiisut, la langue inuit de la côte est du Groenland au xixe siècle - Pierre Robbe; Bernadette Robbe (Revue d'ethnoécologie)
For many years, Pierre Robbe and Bernadette Robbe have been developing an encyclopedic dictionary of tunumiisut, the Inuit language of the east coast of Greenland, one of the dialects spoken today by the Inuit people from the Bering Strait to the east coast of Greenland.Compared to all these dialects, and mainly to the one that is spoken on the west coast of Greenland, Kilaamiusut – the country's official language, to which is close to it - the Tunumiisut lexicon has profoundly evolved during the 19th century.Many words have been replaced with descriptive or metaphorical lexemes, foloowing the pattern that shamans used to not directly name potentially dangerous entities.Leaning on the linguistic history of the Inuit, on archeology, on the study of animal life in relation to the climate, and on the many stories and testimonies that were collected, the authors suggest that understanding this particularism, which certainly results from cultural factors, is nevertheless closely linked to the ecological conditions of this Arctic area (climate, ice, fauna), conditions that fluctuate over time, with prosperous periods and catastrophic phases for animal life and therefore for that of humans, whose existence depended directly on it.